Comprehensive Analysis of Differentially Expressed lncRNA, circRNA and mRNA and Their ceRNA Networks in Mice With Severe Acute Pancreatitis - Wang, Bing; Wu, Jun; Huang, Qilin; Yuan, Xiaohui; Yang, Yi; Jiang, Wen; Wen, Yi; Tang, Lijun; Sun, Hongyu (Frontiers in Genetics, 2021)
Severe acute pancreatitis (SAP) is an acute digestive system disease with high morbidity mortality and hospitalization rate worldwide, due to various causes and unknown pathogenesis. In recent years, a large number of studies have confirmed that non-coding RNAs (ncRNAs) play an important role in many cellular processes and disease occurrence. However, the underlying mechanisms based on the function of ncRNAs, including long noncoding RNA (lncRNA) and circular RNA (circRNA), in SAP remain unclear. In this study, we performed high-throughput sequencing on the pancreatic tissues of 3 normal mice and 3 SAP mice for the first time to describe and analyze the expression profiles of ncRNAs, including lncRNA and circRNA. Our results identified that 49 lncRNAs, 56 circRNAs and 1194 mRNAs were differentially expressed in the SAP group, compared with the control group. Furthermore, we performed Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of differentially expressed lncRNAs and circRNAs, and found that the functions of the parental genes are enriched in the calcium-regulated signaling pathway, NF-κB signaling pathway, autophagy and protein digestion and absorption processes, which are closely related to the central events in pathogenesis of SAP. We also constructed lncRNA/circRNA-miRNA-mRNA networks to further explore their underlying mechanism and possible relationships in SAP. We found that in the competitive endogenous RNA (ceRNA) networks, differentially expressed lncRNAs and circRNAs are mainly involved in the apoptosis pathway and calcium signal transduction pathway. In conclusion, we found that lncRNAs and circRNAs play an important role in the pathogenesis of SAP, which may provide new insights in further exploring the pathogenesis of SAP and seek new targets for SAP.